PERAN INFLUENCER DALAM MEMBENTUK PEMAKNAAN GEN-Z TENTANG KONSUMERISME - Putu Ayu Maharani; Olivia Nadya Lestari; Savina Hayuningtyas (Jurnal Sosiologi UPR, 2025)
This research explores the role of social media influencers in shaping the meaning of Generation Z's perception of consumerism in the digital era. With a qualitative approach and phenomenological methods used, this research utilizes in-depth interviews with Generation Z respondents who have active involvement with influencer content on social media. Research findings show that the role of influencers, by applying strong representations and symbols, is able to build an image of prestige and social identity that influences Generation Z's consumption patterns. By referring to the Simulacra theory put forward by Jean Baudrillard, this research highlights that social media is not only a space mere promotion, but also a tool for creating a new reality that encourages an excessively consumerist lifestyle. Thus, the main conclusion states that the meaning of perceptions regarding consumerist attitudes among Generation Z is influenced by the hyperreality created by influencers on social media, where the symbolic value of a product is more important than its functional value.